2014
DOI: 10.2190/om.69.4.a
|View full text |Cite
|
Sign up to set email alerts
|

Online Survey as Empathic Bridging for the Disenfranchised Grief of Pet Loss

Abstract: The current cross-cultural study investigated grief reactions of bereaved individuals following the death of a pet. We used qualitative methodology to compare, analyze, and report responses of U.S. and French Canadian participants to the last open-ended question on our online pet loss survey. We explored the degree to which our data illustrated pet loss as disenfranchised grief and asked whether there are differences and commonalities in the expression of grief between the two samples. Four major themes emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…Within our research, (Packman et al 2014) men have frequently reported that they grieve more for their animal companion than they did for some humans. This finding is corroborated by our clinical experience and underscores the strong connection between men and their dogs.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Within our research, (Packman et al 2014) men have frequently reported that they grieve more for their animal companion than they did for some humans. This finding is corroborated by our clinical experience and underscores the strong connection between men and their dogs.…”
Section: Discussionmentioning
confidence: 74%
“…Counselors must not trivialize pet loss and grief, as too often, clients' experience is disenfranchised and minimized (Packman et al 2014). Clients have reported clinicians looking to uncover the "real reason" for the grief, either within their family or within areas of dysfunction in personal or professional relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, appropriate retirement minimizes the chance of an acute and sudden death of the animal. Informing a participant that a therapy animal has passed away is tragic and unsettling, especially since the participant was not prepared to say goodbye to the animal before death [51,53]. Retirement facilitates a peaceful goodbye and closure for the participant.…”
Section: For the Human Participantsmentioning
confidence: 99%
“…Unfortunately, as our four-legged companions have relatively short lifespans, an inevitable aspect of companion animal ownership is companion animal loss and millions of Americans will mourn for their companion animals annually [4]. Grieving a companion animal can be an intense emotional process, resulting in feelings of sadness, despair, and numbness.…”
Section: Introductionmentioning
confidence: 99%